Monocytes Undergo Functional Reprogramming to Generate Immunosuppression through HIF-1α Signaling Pathway in the Late Phase of Sepsis. (7th February 2020) - Li, Li-Li; Dai, Bing; Sun, Yu-Han; Zhang, Ting-Ting
Abstract : Severe pneumonia with sepsis is characterized by a dysregulated inflammatory response of endotoxin. In our study, we attempted to investigate the roles of the immune guardian cells (monocytes) in the immune-inflammatory response of severe pneumonia-induced sepsis. We performed analysis in the blood samples of human and animals with ELISA, western blot, flow cytometry (FCM) methods, etc. Results showed that the proinflammatory status shifted to hypoinflammatory phases during the sepsis process. In a clinical study, the levels of IL-1 β, IL-6, TNF- α, etc., except for IL-10, were inhibited in the late phase of sepsis, while, in an animal study, the immune suppression status was attenuated with administration of the adenovirus Ade-HIF-1 α . Conversely, the amount of IL-10 was lower in the adenovirus Ade-HIF-1 α group compared with the sepsis model group and the Ade-control group. Moreover, in the clinical study, the programmed cell death-ligand 1 (PD-L1) was overexpressed in monocytes in the late phase of sepsis, while the expression of proteins HIF-1 α and STAT3 was decreased in the late phase of sepsis. However, in the animal study, we found that the HIF-1 α factor facilitated the inflammatory response. The expression of the proteins HIF-1 α and STAT3 was increased, and the PD-L1 protein was decreased with the adenovirus Ade-HIF-1 α administration compared with the rats without Ade-HIF-1 α injection and with the Ade-control injection. Additionally, the proteins HIF-1 α and STAT3 were coregulated at transcriptional levels during the inflammatory responses of sepsis. Taken together, monocytes undergo reprogramming to generate immunosuppression through the HIF-1 α signaling pathway in the late phase of sepsis.